PENGARUH EFIKASI DIRI GURU TERHADAP KINERJA GURU-GURU SMK DI KECAMATAN BUMIJAWA KABUPATEN TEGAL - iin kurniasih; Ilham Susilo Bakti (STKIP NU Kabupaten Tegal, 2022)
This study aims to analyze the influence of teacher self-efficacy on teacher performance in SMK teachers in Bumijawa District, Tegal Regency. This type of research is explanatory research with a quantitative approach. The population in this study were vocational school teachers in Bumijawa District, Tegal Regency with a total population of 112 people. All members of the population are used as respondents. Of the 112 questionnaires distributed, 109 questionnaires were returned. Based on the instrument test, namely the validation test and reliability test, valid and reliable indicators have been obtained for further analysis. The regression model was tested with the coefficient of determination test and the F test. Based on the F test, it was found that the model was feasible for further analysis. The results of the test for the coefficient of determination illustrate that the contribution of the independent variables has no significant effect on the dependent variable. The hypothesis was tested using the t test using Moderation Regression Analysis (MRA). The results of the study show that self-efficacy has effect on teacher performance.